1998
DOI: 10.1093/jn/128.1.50
|View full text |Cite
|
Sign up to set email alerts
|

Intakes of High Fat and High Carbohydrate Foods by Humans Increased with Exposure to Increasing Altitude During an Expedition to Mt. Everest

Abstract: The objectives of the study were to determine total energy intakes, distribution of energy derived from the macronutrients, and the effects of increasing altitudes on energy and macronutrient consumption during exposure to high altitudes. High fat, low carbohydrate diets (35% and 50% of energy, respectively) or low fat, high carbohydrate diets (20% and 65% of energy, respectively) were provided to two groups of subjects for a 3-wk period. Groups then consumed the alternate diet for 3 wk, followed by a return t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
28
0
2

Year Published

2001
2001
2018
2018

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(31 citation statements)
references
References 17 publications
1
28
0
2
Order By: Relevance
“…In terms of macronutrient provision, some evidence suggests that a preference for meals high in carbohydrate occurs at HA [37] while another study showed climbers preferentially chose highfat diets [62]. Fat is the most energy dense macronutrient (an important consideration in the development of ration packs), but yields less energy per unit oxygen consumed when compared to carbohydrate (4.69 kcal l -1 vs. 5.05 kcal l -1 ) a highly relevant fact in the oxygen-poor environment of HA [63].…”
Section: Ne Hill Mj Stacey Dr Woodsmentioning
confidence: 99%
“…In terms of macronutrient provision, some evidence suggests that a preference for meals high in carbohydrate occurs at HA [37] while another study showed climbers preferentially chose highfat diets [62]. Fat is the most energy dense macronutrient (an important consideration in the development of ration packs), but yields less energy per unit oxygen consumed when compared to carbohydrate (4.69 kcal l -1 vs. 5.05 kcal l -1 ) a highly relevant fact in the oxygen-poor environment of HA [63].…”
Section: Ne Hill Mj Stacey Dr Woodsmentioning
confidence: 99%
“…Um estudo que avaliou o consumo dos diferentes macronutrientes em altitudes crescentes, entretanto, demonstrou uma tendência de aumento no consumo tanto de alimentos ricos em carboidrato como de alimentos ricos em gordura 37 . O mais recomendável, então, seria não excluir alimentos saborosos ricos em gordura, já que são fontes ricas em energia, que podem ajudar no fornecimento da necessidade energética aumentada na altitude.…”
Section: Energia E Macronutrientesunclassified
“…O mais recomendável, então, seria não excluir alimentos saborosos ricos em gordura, já que são fontes ricas em energia, que podem ajudar no fornecimento da necessidade energética aumentada na altitude. Queijo, peixes enlatados em óleo, chocolate, entre outros, preenchem os critérios de alimentos ricos em gordura, que são facilmente preparados para o consumo 37 .…”
Section: Energia E Macronutrientesunclassified
“…A number of explanations have been proposed including anorexia, elevated basal metabolic rate, body water loss, and altered satiety hormones. However, the majority of studies support that altitude-induced weight loss is largely a function of negative energy balance secondary to inadequate energy intake [1,2,3,4,5,6,7,8,9]. Energy expenditure is elevated at altitude and is equivalent to moderate to high intensity exercise conducted at sea level [3].…”
Section: Introductionmentioning
confidence: 99%
“…Energy expenditure is elevated at altitude and is equivalent to moderate to high intensity exercise conducted at sea level [3]. When this energy expenditure is combined with suboptimal energy intakes of 50%–70% of daily requirements weight loss occurs [1,2,3,4,5,6,7,8,9]. …”
Section: Introductionmentioning
confidence: 99%